2006
DOI: 10.1098/rsif.2006.0186
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of basic control measures, antivirals and vaccine in curtailing pandemic influenza: scenarios for the US, UK and the Netherlands

Abstract: An increasing number of avian flu cases in humans, arising primarily from direct contact with poultry, in several regions of the world have prompted the urgency to develop pandemic preparedness plans worldwide. Leading recommendations in these plans include basic public health control measures for minimizing transmission in hospitals and communities, the use of antiviral drugs and vaccination. This paper presents a mathematical model for the evaluation of the pandemic flu preparedness plans of the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 33 publications
2
83
0
2
Order By: Relevance
“…Mathematical models, used together with historical studies of data on the 1918 flu pandemic in the United States, have advanced the proposition that community-wide application of NPIs may have been the main factor responsible for the varying degrees of impact experienced by U.S. municipalities in the 1918 pandemic. These studies also suggested that NPI effectiveness was contingent on timely implementation and consistent compliance (7,9,10), and that early relaxation of these measures may have been responsible for re-ignition of pandemic waves. Perhaps the most germane and compelling study is the work of Markel et al (11)(12)(13), which concluded that nothing except protective isolation measures worked in containing the second wave of the 1918 pandemic in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical models, used together with historical studies of data on the 1918 flu pandemic in the United States, have advanced the proposition that community-wide application of NPIs may have been the main factor responsible for the varying degrees of impact experienced by U.S. municipalities in the 1918 pandemic. These studies also suggested that NPI effectiveness was contingent on timely implementation and consistent compliance (7,9,10), and that early relaxation of these measures may have been responsible for re-ignition of pandemic waves. Perhaps the most germane and compelling study is the work of Markel et al (11)(12)(13), which concluded that nothing except protective isolation measures worked in containing the second wave of the 1918 pandemic in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…A sporadic, but steadily larger series of human cases of H5N1 avian influenza with a case fatality rate Ͼ50% stands as a harbinger of the devastating potential a novel influenza virus might pose. To validate estimates of mortality and morbidity, and to explore options for the control of an influenza pandemic, several researchers have modeled both the process of influenza transmission and various intervention measures aimed at mitigating its consequences (1)(2)(3)(4)(5)(6)(7). Many of these studies suggest that antiviral pharmaceutical agents and vaccines would be the most effective interventions, with nonpharmaceutical interventions (NPIs) relegated to a subordinate, incremental role.…”
mentioning
confidence: 99%
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. (Normile, 2005b) Not relevant outcomes (Nuño et al, 2007) Study population (Olivier, 2005) Territory (Oluwayelu et al, 2015) Territory (Onihshenko, 2008) Language ( (Peterson et al, 2007) Territory (Petrauskene et al, 2010) Not relevant outcomes (Peyre et al, 2007) Territory (Peyre et al, 2009) Not relevant outcomes (Phan et al, 2013) Not relevant outcomes (Philippa et al, 2005) Not relevant outcomes (Philippa et al, 2007) Not relevant outcomes (Pillai et al, 2008) Not relevant outcomes (Poetri et al, 2009) Not relevant outcomes (Poon et al, 2009) Not relevant outcomes (Probst et al, 2012) Not relevant outcomes (Prosser et al, 2011) Territory (Puzelli et al, 2005) Study population (Qiao et al, 2006) Not relevant outcomes (Rabinowitz et al, 2012) The present document has been produced and adopted by the bodies identified above as authors. This task has been carried out exclusively by the authors in the context of a contract between the European Food Safety Authority and the authors, awarded following a tender procedure.…”
Section: Citation Reason Of Exclusionmentioning
confidence: 99%
“…In developing countries like Ethiopia it can causes great economic loss due to its treatment and control cost. However, we can control the impacts of swine flu using vaccination, use of antivirals for prophylaxis, use of antivirals for treatment and other simple measures like standard precautions, particularly respiratory and cough hygiene [11]. Taking this fact into account, the objective of this study paper is: a.…”
Section: Introductionmentioning
confidence: 99%